Determinants of repurchase intention in the Indonesian e-commerce platforms - Lukman Zaini Abdullah; Nanang Apriliyanto; Sherli Junianingrum (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to investigate the influence of e-service quality, customer trust, and customer satisfaction on repurchase intention in the Indonesian e-commerce platforms.Method — The type of research used is causal research, which examines the relationship between variables through quantitative research. The number of samples in this study was 250 respondents. The sample for this research includes Indonesian citizens aged more than 17 years old, who are users of the Tokopedia, Shopee, and Lazada platforms on their smartphones. This study uses primary data filled out by respondents through Google Forms and focuses on research variables, which include e-service quality, customer trust, customer satisfaction, and repurchase intention. The data that have been obtained were analyzed using the Structural Equation Modeling (SEM) technique.Result — The results of this study indicate that e-service quality has a significant positive effect on customer trust and customer satisfaction. In addition, the relationship between customer trust and customer satisfaction on repurchase intention also has a significant positive influence.Contribution — This study offers a valuable academic contribution by enhancing and advancing theories associated with repurchase intention within the context of e-commerce platforms in Indonesia. Furthermore, this study addresses a significant gap in the existing literature by explicitly defining the scope and object of investigation, thereby refining the clarity and comprehensiveness of the research landscape.